The Relationship between Organizational Commitment, Self-Efficacy, and Work Motivation with Employee Loyalty at Kana Tamita and Mawar Gas Stations, Langsa City - Pratiwi, Rosi; Padang, Horas; Butar - Butar, Ernita Christin; Hutapea, Lambok; Lubis, Rosidah; Yusrita, Yusrita (Universitas Medan Area, 2024)
This study aims to analyze the relationship between organizational commitment, self-efficacy, work motivation, and employee loyalty at Kana Tamita and Mawar petrol stations, in Langsa City. The research uses a quantitative approach with a survey technique through questionnaires. A total of 46 employees became respondents in this study. Data analysis was carried out using multiple linear regression to determine the influence of each variable on employee loyalty. The results of the study show that organizational commitment, self-efficacy, and work motivation have a positive and significant effect on employee loyalty. Organizational commitment has the most dominant influence compared to other variables, followed by work motivation and self-efficacy. Simultaneously, these three variables explain 56.2% of the variation in employee loyalty. These findings indicate that increased organizational commitment, self-efficacy, and work motivation can increase employee loyalty. Therefore, companies are advised to strengthen their commitment and motivation development programs and increase employee self-efficacy to maintain their loyalty in the long term.